Effect of Recycling Agents on Rheological and Micromechanical Properties of SBS-Modified Asphalt Binders. (30th December 2018) - Guo, Meng; Tan, Yiqiu; Luo, Daisong; Li, Yafei; Farooq, Asim; Mo, Liantong; Jiao, Yubo
Abstract : Individual effect of aging and rejuvenator recycling on basic properties of asphalt is readily recognized, but there is only limited understanding about whether the recycling of SBS- (styrene-butadiene-styrene-) modified asphalt is an inverse process of aging or not. To compare the effects of aging and rejuvenator on microproperties and molecular composition of SBS-modified asphalt, comprehensive performance tests and physical-chemistry experiments were conducted. The results of infrared spectroscopy tests demonstrate that the reticular crosslinking structure of asphalt was destroyed and SBS's modification effect was gradually lost after aging. This can cause the strengthening of high-temperature performance and reduction of the low-temperature anticrack property of SBS-modified asphalt. Scanning electron microscope shows that the island structure of SBS-modified asphalt disappeared after aging. Energy spectrum analysis shows that the C (carbon) content of aged SBS-modified asphalt has decreased, while the O (oxygen) content and S (sulfur) content have increased obviously. Results of the fluorescence microscope, SEM, and rheological tests show that the epoxy functional group compounds of aliphatic glycidyl ether resin had high reactivity; the triblock molecular structure of SBS and the mechanical performance of SBS-modified asphalt were recovered.